Fluorescently labeled cyclodextrin derivatives as exogenous markers for real-time transcutaneous measurement of renal function - Huang, Jiaguo; Weinfurter, Stefanie; Pretze, Marc; Kränzlin, Bettina; Pill, Johannes; Gretz, Norbert (Bioconjugate chemistry, 2016)
Evaluation of renal function is crucial for a number of clinical situations. Here, we reported a novel exogenous fluorescent marker (FITC-HPβCD) to real-time assess renal function by using a transcutaneous fluorescent detection technique. FITC-HPβCD was designed based on the principle of renal clearance of designed drugs. It displays favorable fluorescent properties, high hydrophilicity, low plasma protein binding, and high stability in porcine liver esterase as well as in plasma and nontoxicity. More importantly, FITC-HPβCD can be efficiently and rapidly filtered by glomerulus and completely excreted into urine without proximal tubular reabsorption or secretion in rat models. Additionally, the marker was well-tolerated, with nearly 100% urinary recovery of the given doses, and no metabolism were found. Relying on this novel kidney function marker and transcutaneous devices, we demonstrate a rapid, robust, and convenient approach for real-time assessing renal function without the need of time-consuming blood and urine sample preparation. Our work provides a promising tool for noninvasive real-time monitoring of renal function in vivo.